yolanda.abellia@yahoo.com - Yolanda Yolanda (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research aims to test the influence about fundamental factors which is consisting of Retrun on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) to share price. The sample of this research is the manufacture company which is registered in Indonesian Stock Exchange during 2012 - 2016. This research uses 12 samples which is choosen by purposive sampling method. The results showed that ROA and NPM have positive but unsignifcant effect on price share, ROA has positive and significant effect on price share, and DER has negative and unsignificant effect on price share. ROA, ROE, DER, and NPM all simultaneously have significant effect on price share. Moreover, the result that has been obtained by using R-Square is 90,41% and the remaining 9,59 % influenced by other factors.